Conceptions of Territories. Indigenous Land Management and Multinational Property in the Northwest Territories of Canada - Linda Armano (Tab Edizioni, 2022)
While the existing analyses on Canadian ethical diamonds focus primarily on the decision-making criteria of consumers at the time of purchase, little is known about the mining context from which these stones come. The book aims to fill these gaps by concentrating the analysis on the diamond mines in the Northwest Territories from which ethical diamonds are extracted. Based on the debate between the macroeconomics of diamonds and Indigenous microeconomics in the Canadian region, this monograph will focus primarily on the specific aspect of the social, economic, and political change experienced by the Indigenous communities of the Northwest Territories produced by colonisation.